CAROTID ARTERY EXTERIORIZATION IN BROWN BROCKET DEER (MAZAMA GOUAZOUBIRA) FOR AN EXPERIMENTAL STUDY of ANESTHESIA - Munerato, Marina Salles [UNESP]; Barbanti Duarte, Jose Mauricio [UNESP]; Marques, Jose Antonio [UNESP] (Amer Assoc Zoo Veterinarians, 2009)
This report evaluates the carotid artery exteriorization technique to allow repeated percutaneous artery catheterization in six brown brocket deer (Mazama gouazoubira). Repeated percutaneous catheterization of the carotid artery was possible for periods of 3 mo to obtain arterial blood and monitor arterial blood pressure of deer without risk of arterial rupture. The artery pulse was easily palpable for periods tip to 15 mo. Postoperative complication and/or arterial damage was not observed.
Keywords: Blood collection; Brown brocket deer; carotid exteriorization; Mazama gouazoubira; percutaneous catheterization